Pengaruh Modal Manusia Terhadap Tingkat Kemiskinan : Analisis Pendidikan Dan Kesehatan - Venia Zaura; Rusy Dina (Universitas Negeri Padang, 2026)
The purpose of this study is to examine the influence of human capital, measured through education and health indicators, on the poverty rate in Indonesia. The data used in this study were secondary data obtained from the Statistics Indonesia (BPS) across 34 provinces in Indonesia during the period 2015-2024. The research employs a panel data regression approach with the selected model being the Random Effect Model. The results show that education, health, the open unemployment rate, and the provincial minimum wage have an influence on the poverty rate in Indonesia. Improvements in the quality of education and health contribute to reducing poverty through increased productivity and the ability of individuals to obtain income, while unemployment conditions and income levels are important factors affecting the effectiveness of poverty reduction. These findings indicate that strengthening human capital needs to be supported by expanding employment opportunities and improving economic welfare so that poverty allevation strategies can be implemented effectively and sustainably.